2005
DOI: 10.1021/jf0492971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on the Antioxidant Vitamins and Antioxidant Capacity ofVigna sinensisVar. Carilla

Abstract: Cowpea (Vigna sinensis L. var. Carilla) flours obtained by fermentation with inoculum Lactobacillus plantarum (PF) or with the natural microorganisms present in the flour (NF) and subsequent heat treatment in an autoclave were prepared to study the effect of fermentation on the antioxidant vitamin content and on the antioxidant capacity. Bacterial counts and pH values, vitamins C and E, carotenoids, glutathione (GSH), superoxide dismutase-like activity (SOD-like activity), peroxyl radical-trapping capacity (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 62 publications
8
54
0
Order By: Relevance
“…Reported PRTC values of raw seeds of lentils, vetch and soybeans were 30, 23 and 7 mM, respectively (Zielinski, 2002). Raw cowpea seeds had a PRTC of 9 mM (Doblado et al, 2005). Direct comparisons of PRTC values should take into consideration the differences in how antioxidant capacities are measured such as sampling preparation and extraction procedures.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Reported PRTC values of raw seeds of lentils, vetch and soybeans were 30, 23 and 7 mM, respectively (Zielinski, 2002). Raw cowpea seeds had a PRTC of 9 mM (Doblado et al, 2005). Direct comparisons of PRTC values should take into consideration the differences in how antioxidant capacities are measured such as sampling preparation and extraction procedures.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…The Trolox Equivalent Antioxidant Capacity (TEAC) determination was carried out in PBS extracts of raw, germinated and fermented chickpeas according to Re et al (1999) and Doblado et al (2005). This assay was based on the reduction of the ABTS þ radical cation by antioxidants present in the extracts measured at 734 nm at 37 C for 10 min (Beckman DU-70, model 150, series 1574, USA).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Of particular importance, it has been recently reported that the consumption of medicinal plant extracts may exert positive effects on different models of human disorders (Martins et al 2012, Courtes et al 2015, Salgueiro et al 2016. Accordingly, consumption of plant extracts supplies active compounds that may have different beneficial functions in the body (Doblado et al 2005, Oboh 2005. Interestingly, literature data have indicated that the biological properties of different diets can be lost after isolation of specific compounds, indicating that part of their pharmacological properties can be related to a combination of different classes of such compounds (Pietrovski et al 2006, Klimaczewski et al 2014.…”
Section: Introductionmentioning
confidence: 99%